(untitled) (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2009)
This contribution is about a new "Pilgrim’s flask " vase from Veii, increasing the number of thirty similar vases already known from the Tyrrhenian area. This vase, belonging to a disturbed burial, could be dated during the 7th century BC, thanks to other objects found in the surrounding area. According to its formal and technical features, this vase represents an unicum, probably realized by a local atelier. In fact Veian local pottery production in this period shows many experimentations, also conditioned by the greater opening to foreign suggestions.